KAJIAN IKONOMETRI ARCA LOGAM PRODUK PERAJIN TROWULAN - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 2008)
A question often raised on metal sculpture made by Trowulan artists is: do iconometric aspects of the sculptures follow the iconometric order? Studies on iconology, including iconographic and iconometric studies, are important in Indonesian archaeology. Iconometric study on metal sculptures made by Trowulan artists is an example for iconometric study in Indonesia.